The butoh dance amidst the politics of fear - Martineau, Jonathan (Re-visiones, 2024)
In this article we analyse the opposition between the fear of death and the fear of birth. The politics based on the fear of death implies the construction of a fiction presented and considered as a truth. This fictional truth is sewed within the bodies and generates a ghostly body. The ghost blocks the ongoing birth and therefore facilitates the extension of fear within the bodily tissues and towards the external space. Monsters appear as projection of forgotten body parts. Demons live at the edges of society, which reduces to a minimum the life of its subjects thanks to demoniacal threats. “Terrorist” is today’s word for demon. Continual birth is the last fight, waged by postmodern samurais that live and think the world as a butoh dance.